The prevalence and significance of substance use disorders in bipolar type I and II disorder - Strakowski Stephen M; Cerullo Michael A (BMC, 2007)
Abstract The aim of this paper is to provide a systematic review of the literature examining the epidemiology, outcome, and treatment of patients with bipolar disorder and co-occurring substance use disorders (SUDs). Articles for this review were initially selected via a comprehensive Medline search and further studies were obtained from the references in these articles. Given the lack of research in this field, all relevant studies except case reports were included. Prior epidemiological research has consistently shown that substance use disorders (SUDs) are extremely common in bipolar I and II disorders. The lifetime prevalence of SUDs is at least 40% in bipolar I patients. Alcohol and cannabis are the substances most often abused, followed by cocaine and then opioids. Research has consistently shown that co-occurring SUDs are correlated with negative effects on illness outcome including more frequent and prolonged affective episodes, decreased compliance with treatment, a lower quality of life, and increased suicidal behavior. Recent research on the causal relationship between the two disorders suggests that a subgroup of bipolar patients may develop a relatively milder form of affective illness that is expressed only after extended exposure to alcohol abuse. There has been very little treatment research specifically targeting this population. Three open label medication trials provide limited evidence that quetiapine, aripiprazole, and lamotrigine may be effective in treating affective and substance use symptoms in bipolar patients with cocaine dependence and that aripiprazole may also be helpful in patients with alcohol use disorders. The two placebo controlled trials to date suggest that valproate given as an adjunct to lithium in bipolar patients with co-occurring alcohol dependence improves both mood and alcohol use symptoms and that lithium treatment in bipolar adolescents improves mood and SUD symptoms. Given the high rate of SUD co-occurrence, more research investigating treatments in this population is needed. Specifically, double blind placebo controlled trials are needed to establish the effectiveness of medications found to be efficacious in open label treatments. New research also needs to be conducted on medications found to treat either bipolar disorder or a SUD in isolation. In addition, it may be advisable to consider including patients with prior SUDs in clinical trials for new medications in bipolar disorder.